Essential requirements for terminal equipment intended for connection to unstructured digital leased circuits of the public telecommunications network using a CCITT Recommendation G.703 interface at a rate of 8448 kbit/s with a 75 ohms unbalanced presentation. (15th November 1994) - British Standards Institution,
No abstract available